Multi-Distributed Activation Energy Model for Pyrolysis of Sugarcane Bagasse: Modelling Strategy and Thermodynamic Characterization - Siti Jamilatun; Muhammad Aziz; Joko Pitoyo (Universitas Pendidikan Indonesia, 2023)
The multi-distributed activation energy model (multi-DAEM) is the most effective approach for outlining the kinetics model of biomass pyrolysis. The purpose of this study is to identify the optimal number and shape of the DAEM for sugarcane bagasse pyrolysis and to discuss its thermodynamic characteristics using the combination of multi-DAEM and differential thermal analysis (DTA). The heating rate of 10, 30, and 50 °C/min was employed. The results revealed that the multi-DAEM with five pseudo components and Weibull distribution shape gave the lowest relative root mean of the squared error (RRMSE) of 0.66% and 0.41%, respectively. Kinetic and thermodynamic studies showed that the 1st and 4th pseudo components which represent lignin, have activation energy (E0) of 189.6 and 180.6 kJ/mol, and less endothermic or possibly exothermic properties. Meanwhile, the 2nd, 3rd, and 5th pseudo components which represent cellulose, hemicellulose, and moisture have activation energy (E0) of 176.1, 152.2, and 145.6 kJ/mol, respectively, and endothermic properties.